Professional update. The 1999 ACC task analysis of nurse-midwifery/midwifery practice phase I: the instrument development study. - Fullerton JT; Johnson P; Oshio S (Journal of Midwifery & Women's Health)
The national certification examination (NCE) in nurse-midwifery and midwifery is developed, administered, and evaluated by the ACNM Certification Council (ACC). The blueprint for the NCE is based upon a comprehensive list of tasks that describe the knowledge, skills, and abilities expected of the midwifery practitioner at entry into the profession. In 1999, the ACC initiated the third in a series of task analysis studies to ensure the currency and relevance of the task list. This study was considered particularly timely, given that the professional organization, the American College of Nurse-Midwives, had approved pathways to midwifery for individuals whose first degree was not in nursing (the certified midwife) and also had expanded the core competencies for midwifery practice to include responsibilities in the domain of primary care. This manuscript reports the results of the pilot study, in which the specific list of tasks was developed. Three hundred and six ACNM members responded to a preliminary list of tasks, indicating their opinions about whether each specific task was relevant to entry-level midwifery practice. The task list finally derived among seven domains of practice (antepartum, intrapartum, newborn, postpartum, well-women/gynecology, primary care/health assessment, and professional issues.) The task list represents a comprehensive profile of entry-level practice for nurse-midwives and midwives certified by the ACC.